Il processo di laicizzazione delle religious offences in Inghilterrae Galles: tra prospettiva storica e comparazione (Stato, Chiese e pluralismo confessionale, 2012)
Contributo sottoposto a valutazioneSOMMARIO. 1. Introduzione. I diversi modelli dell’attuale tutela penale della religione negli ordinamenti italiano e britannico – 2. Rapporti Stato-Chiesa e secolarizzazione delle fonti delle religious offences: l’età delle riforme religiose – 3. Il Settecento: tra laicizzazione del diritto penale ed “istituzionalizzazione” della religione dominante – 4. L’avvio di una laicizzazione dei contenuti delle religious offences nel XIX secolo – 5. Tutela penale, rapporti tra Stato e Chiese e pluralismo religioso nel XX secolo – 6. Osservazioni conclusive.:Abstract The path of secularization of religious Offences in England and Wales: between historical and comparative perspective In recent years in Italy and England some important reforms concerning the traditional criminal offences against religion have been introduced: in Italy, Law 85/2006 regarding crimes against religious denominations that has changed the offence of vilifying, without changing the blasphemy offence; in England and Wales, the Racial and Religious Hatred Act 2006, the repeal of the common law of blasphemy and blasphemous libel in 2008 and the offences of defamatory, seditious and obscene libel in 2009. The historical perspective allows us to contextualize the hallmarks by which the two nations deal with the problem of offences against religion. The historical path that led to the current British reforms, in fact, was characterized by the transition from the institutionalized model of protection under criminal law of the Church of England, as established Church, to the formal and substantive secularization of religious Offences, which finally led to their abolition, without questioning - at least formally - the general system of the Established Church of England. The differences between the two models of criminal protection of religion are rooted in that path and are reflected in the more general legal treatment of religion and in the state/churches/religions relations in the two countries